Minority Muslims and freedom of religion: Learning from Australian Muslims’ Experiences - Syamsul Arifin; Hasnan Bachtiar; Ahmad Nur Fuad; Tongat Tongat; Wahyudi Wahyudi (IAIN Salatiga, 2019)
This article aims at diagnosing the development of Ummah while Muslims are living as minority in Australia. Through a sociological approach, qualitatively, some issues considered in understanding the development are practices of secularism, multiculturalism and protection of human rights. This academic framework in comprehending the development might be claimed as a new trajectory of sociological exploration. Accordingly, this study is proposed to become a preliminary research on Muslims’ freedom of religion living in secular country. This article finds that Australia is a state that consistently has protected its citizens’ freedom of religion and the Australian government, in dealing with social and religious issues, and law enforcement, has worked professionally. However, Muslims have faced challenging realities of cases of discrimination coming from fundamentalist Christians. The cases, indeed, can be mitigated through inter-religious dialogue and cooperation. This article argues that, so far, the development of Ummah in the country has been running well. Under the protection of a secular state, minority Muslims in Australian multicultural societies can enjoy their freedom of religion. Practices of inter-religious tolerance are stronger than the tensions and conflicts have happened.. Artikel ini bertujuan untuk mendiagnosa kondisi pembangunan umat ketika kaum Muslim hidup sebagai minoritas di Australia. Melalui pendekatan sosiologis, secara kualitatif, pelbagai isu yang dipertimbangkan adalah praktik sekularisme, multikulturalisme dan penegakan HAM. Kerangka kerja yang demikian dalam memandang pembangunan umat, dapat diklaim sebagai hal yang baru. Karena itu, studi ini diusulkan sebagai studi pendahuluan mengenai elaborasi sosiologis terhadap kebebasan beragama minoritas Muslim yang hidup di negara sekular. Artikel ini menemukan bahwa Australia adalah negara yang secara konsisten melindungi kebebasan beragama warga negaranya dan pemerintahnya bekerja secara profesional terutama dalam penegakan hukum. Tetapi, kasus-kasus diskriminasi masih terjadi, terutama oleh Kristen fundamentalis terhadap kaum Muslim. Tentu saja hal itu dapat dimitigasi melalui dialog dan kerjasama antar agama. Artikel ini berargumentasi bahwa, sejauh ini kondisi pembangunan umat berjalan dengan baik. Di bawah perlindungan negara sekular, Muslim minoritas yang hidup di tengah masyarakat multikultural dapat menikmati kebebasan beragama. Praktik-praktik toleransi yang ada, lebih kuat ketimbang tensi dan konflik antar-agama yang terjadi.